(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The purpose of the elongation process is to reduce the linear density of the product by decreasing the number of fibers in its cross-section through pushing the fibers relative to each other. The essence of stretching is to increase the speed of the fibers’ movement and allow them to shift relative to each other, redistributing the fibers.